Intestinal Epithelial Cells Respond to Chronic Inflammation and Dysbiosis by Synthesizing H2O2 - Burgueño, Juan F.; Fritsch, Julia; Santander, Ana M.; Brito, Nivis; Fernández, Irina; Pignac-Kobinger, Judith; Conner, Gregory E.; Abreu, Maria T. (Frontiers in Physiology, 2019)
The microbes in the gastrointestinal tract are separated from the host by a single layer of intestinal epithelial cells (IECs) that plays pivotal roles in maintaining homeostasis by absorbing nutrients and providing a physical and immunological barrier to potential pathogens. Preservation of homeostasis requires the crosstalk between the epithelium and the microbial environment. One epithelial-driven innate immune mechanism that participates in host-microbe communication involves the release of reactive oxygen species (ROS), such as hydrogen peroxide (H2O2), towards the lumen. Phagocytes produce high amounts of ROS which is critical for microbicidal functions; the functional contribution of epithelial ROS, however, has been hindered by the lack of methodologies to reliably quantify extracellular release of ROS. Here, we used a modified Amplex Red assay to investigate the inflammatory and microbial regulation of IEC-generated H2O2 and the potential role of Duox2, a NADPH oxidase that is an important source of H2O2. We found that colonoids respond to interferon-γ and flagellin by enhancing production of H2O2 in a Duox2-mediated fashion. To extend these findings, we analyzed ex vivo production of H2O2 by IECs after acute and chronic inflammation, as well as after exposure to dysbiotic microbiota. While acute inflammation did not induce a significant increase in epithelial-driven H2O2, chronic inflammation caused IECs to release higher levels of H2O2. Furthermore, colonization of germ-free mice with dysbiotic microbiota from mice or patients with IBD resulted in increased H2O2 production compared with healthy controls. Collectively, these data suggest that IECs are capable of H2O2 production during chronic inflammation and dysbiotic states. Our results provide insight into luminal production of H2O2 by IECs as a read-out of innate defense by the mucosa.